Comparative Study Between Bahasa Indonesia Textbook for X Grade Published by The Ministry of Education and Culture and Tiga Serangkai Private Publisher - Ika Rahma Yuwanti; Mahsun Mahsun; Sudirman Sudirman (Indonesian Language and Literature Education Study Program and LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2019)
This study focuses on analyzing the quality of Indonesian textbooks for the 2013 Curriculum in class X that published by the government and private publishers (Tiga Serangkai). The analysis will be based on content quality, language quality, presentation quality, and graphic quality. This research is comparative descriptive research, which means this research will describe and compare the two Indonesian textbooks. The method of data collection that used in this study are observation, documentary, and recording. After all data has been collected, it is then analyzed using comparative descriptive analysis based on the Badan Nasional Standar Pendidikan (BNSP). Based on the results of data analysis, it was concluded that almost all Indonesian language books published by the government and private publishers were in accordance with BNSP provisions which are (1) quality of content, (2) quality of language, (3) quality of presentation, and (4) quality of graphics.